2014
DOI: 10.1159/000358666
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genomic DNA Methylation Levels in Human Placenta using Liquid Chromatography-Electrospray Ionization Tandem Mass Spectrometry

Abstract: Background: DNA-methylation is a common epigenetic tool which plays a crucial role in gene regulation and is essential for cell differentiation and embryonic development. The placenta is an important organ where gene activity can be regulated by epigenetic DNA modifications, including DNA methylation. This is of interest as, the placenta is the interface between the fetus and its environment, the mother. Exposure to environmental toxins and nutrition during pregnancy may alter DNA methylation of the placenta a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Therefore, one of the ways in which LAQ824 treatment improved the in vitro developmental competence of porcine SCNT embryos may be that increased histone acetylation levels, caused by promotion of HATs and inhibition of HDAC activities, may facilitate chromatin opening. DNA methylation, as another epigenetic marker [43], also plays an important role in the process of reprogramming and influences in vitro developmental competence of SCNT embryos via the activity of DNA methyltransferases (DNMTs). In this study, we revealed that LAQ824 treatment downregulated the mRNA expression of DNMT1, 3a and 3b in blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one of the ways in which LAQ824 treatment improved the in vitro developmental competence of porcine SCNT embryos may be that increased histone acetylation levels, caused by promotion of HATs and inhibition of HDAC activities, may facilitate chromatin opening. DNA methylation, as another epigenetic marker [43], also plays an important role in the process of reprogramming and influences in vitro developmental competence of SCNT embryos via the activity of DNA methyltransferases (DNMTs). In this study, we revealed that LAQ824 treatment downregulated the mRNA expression of DNMT1, 3a and 3b in blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy microliters of the hydrolised DNA samples were further diluted with 280 μL 0.1 % formic acid to yield a final concentration of 2 ng digested DNA/μL. DNA methylation was assessed by liquid chromatography-electrospray ionization/multi-stage mass spectrometry (LC-ESI/MS/MS) technique as described previously [ 56 ]. LC-ESI/MS/MS was performed with an Agilent 1200 series HPLC system connected to an Agilent 6530 Accurate-Mass Q-TOF instrument with Jet Stream-Interface (Waldbronn, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…1982 , Fuke et al . 2004 ), a large study in 248 placentas has shown that there is a large range of DNA methylation of 2–5% ( Dwi Putra et al . 2014 ), but the reason for this variation requires further investigation.…”
Section: Foetal Sex Differences In Dna Methylationmentioning
confidence: 99%